2016
DOI: 10.1159/000443077
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin Exerts a Delayed Inhibitory Effect on the Proliferation of Cardiomyocytes Derived from Murine ES Cells via Slowing Progression through G2/M Phase

Abstract: Objective: Puerarin, which shows beneficial and protective effects on cardiovascular diseases, is the main isoflavone extracted from Pueraria lobata (kudzu) root. The aim of this study was to investigate the effects of puerarin on in vitro myocardial proliferation and its underlying mechanism. Methods: Myocardial differentiation of transgenic embryonic stem (ES) cells was performed by embryoid body-based differentiation method. The proliferation assay of cardiomyocytes (CMs) derived from ES cells (ES-CMs) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
(43 reference statements)
2
5
0
Order By: Relevance
“…Researches demonstrated that signal pathways such as PI3K/Akt and MAPK/ERK were involved in biological activities of puerarin [2, 17, 20, 23]. Consistently, we found that the upregulation of SERCA2a, PLB and Trd induced by puerarin are abolished by inhibitors of both PI3K/Akt and MAPK/ERK signaling, suggesting their roles in puerarin-mediated functional maturation of mES-CMs through SERCA2a.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Researches demonstrated that signal pathways such as PI3K/Akt and MAPK/ERK were involved in biological activities of puerarin [2, 17, 20, 23]. Consistently, we found that the upregulation of SERCA2a, PLB and Trd induced by puerarin are abolished by inhibitors of both PI3K/Akt and MAPK/ERK signaling, suggesting their roles in puerarin-mediated functional maturation of mES-CMs through SERCA2a.…”
Section: Discussionsupporting
confidence: 87%
“…ES cell-derived CMs (ES-CMs) are widely accepted as a promising resource for cell replacement therapy of cardiac disease and a powerful model for investigating the development, maturation as well as pathological remodeling of heart [1-2]. However, accumulating data suggest that current culture system produces primitive ES-CMs with undeveloped structure and contractile function [1, 3-4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative real-time PCR was performed in the CFX Connect™ Real-Time PCR Detection System (Bio-Rad, USA) by using TB Green TM Premix Ex Taq TM (TAKARA, Japan). The CT values were normalized to GAPDH expression, and mRNA expressions were calculated via 2 −ΔΔCt method as described in previous research 20 . The primers used in present study are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The transgenic mESCs (clone αPIG44) was maintained as previously described [24]. Briefly, undifferentiated mESCs were cultured in IMDM containing 15% FCS, 1% nonessential amino acids, 2mM L-glutamine, 0.1 mM β-mercaptoethanol, 100 U/mL penicillin, 100 µg/mL streptomycin and 1000 U/mL leukemia inhibitory factor (LIF, Chemicon).…”
Section: Methodsmentioning
confidence: 99%